Harmoni Manusia, Alam, dan Tuhan dalam Praktik Tri Hita Karana pada Pendidikan Lingkungan Hidup di Desa Krisik - Raharjo, Sukirno Hadi; Ningrum, Siti Utami Dewi; Masbukhin, Faizal Akhmad Adi (Jurnal Penelitian Agama Hindu, 2025)
Environmental awareness poses a significant challenge for many communities in Indonesia, including the Hindu community in Krisik Village, Gandusari District, Blitar Regency. The concept of Tri Hita Karana, which emphasizes harmony between humans, nature, and God, offers a holistic approach to environmental education. This study aims to explore the implementation of Tri Hita Karana in environmental education and how community collaboration can strengthen this harmony. Using a qualitative method with a case study approach, data was collected through in-depth interviews with community leaders, teachers, and community members, and through participatory observation and document analysis. The findings reveal that the application of Tri Hita Karana in environmental education in Krisik Village has significantly increased community awareness and involvement in environmental conservation. Practices such as waste management, reforestation, and religious ceremonies that honor nature have become integral parts of daily life. Collaboration between schools, village government, and the local community has proven effective in supporting sustainable environmental initiatives. Furthermore, the values of Tri Hita Karana have helped the community develop a more sustainable approach to the environment, strengthening social and spiritual bonds within the community. This study concludes that a local wisdom-based approach like Tri Hita Karana can serve as an effective model in environmental education, contributing significantly to the development of sustainable and culturally rooted environmental education policies.